Aggregation and Phase Separation Phenomenon of Amitriptyline Hydrochloride Under the Influence of Pharmaceutical Excipients. Issue 1 (5th March 2013) - Rub, Malik Abdul; Asiri, Abdullah M.; Sheikh, Mohmad Shafi; Azum, Naved; Khan, Anish; Khan, Aftab Aslam Parwaz; Rahman, Mohammed M.; Kabir‐ud‐Din,
Abstract: The interaction between the amphiphilic drug amitriptyline hydrochloride (AMT) and the nonionic surfactants used in drug delivery has been investigated. Herein, we report the micellization behavior of AMT in presence of ethoxylated alkyl phenols in aqueous medium and the clouding phenomenon in the absence and presence of different nonionic surfactants in buffer solution. The values of critical micelle concentration (CMC) of AMT obtained using the conductivity method, decrease as nonionic surfactant concentration increases. With an increase in temperature, the CMC first increases and then decreases. At 303.15 K, the maximum CMC values were obtained with or without nonionic surfactant. The results obtained indicate attractive interactions (synergism) between the two mixing amphiphiles in solution. The experimentally obtained critical micelle concentration (CMC) values are always lower than ideal CMC values. Micellar mole fraction ( X 1 ) values, calculated by different proposed models, show the contribution of nonionic surfactant concentration. At a fixed drug concentration (50 mmol kg −1 ) and pH (=6.7) nonionic surfactants show continuous increase in cloud point (CP). Increase in drug concentration and pH, in the presence of fixed amounts of nonionic surfactant, increases and decreases the CP, respectively.